Antibacterial Activity Test Of Extract, N-Hexane Fraction, Ethyl Acetate, And Water Of Tangkalak Guava Leaves (Bellucia Pentamera Naudin) Against Staphylococcus Epidermidis ATCC 12228 Bacteria - Elman Maulana; ⁠Tatiana Siska Wardani; ⁠Bagas Ardiyantoro (International Journal of Health Engineering and Technology, 2026)
Skin infections by Staphylococcus epidermidis ATCC 12228 are increasing due to antibiotic resistance, while guava leaves (Bellucia pentamera Naudin) have antibacterial potential based on traditional use and phytochemical content. To evaluate the antibacterial activity of ethanol extract and n-hexane, ethyl acetate, and water fractions of guava leaves against S. epidermidis ATCC 12228. In vitro experimental with disc diffusion, liquid dilution (MIC), and solid dilution (MBC) methods. McFarland 0.5 bacterial suspension (1.5x10^8 CFU/mL); 500 g of leaf simplicia powder from Galing Village, Sambas. Analytical balance, rotary evaporator, SPSS 27 (Shapiro-Wilk, Levene, Kruskal-Wallis, Tukey post-hoc). Ethanol extract inhibited 3.43-6.86 mm (weak-moderate); ethyl acetate fraction 3.67-5.42 mm (most active); MIC 20%; positive for alkaloids, flavonoids, tannins, saponins. Ethanol extract and ethyl acetate fraction have the potential as alternative antibacterial candidates for nosocomial infections.